1980
DOI: 10.1073/pnas.77.7.4180
|View full text |Cite
|
Sign up to set email alerts
|

Scale-invariance in reaction-diffusion models of spatial pattern formation.

Abstract: We propose a reaction-diffusion model of spatial pattern formation whose solutions can exhibit scaleinvariance over any desired range for suitable choices of parameters in the model. The model does not invoke preset polarity or any other adboc distinction between cells and provides a solution to the French flag probleit without sources at the boundary. Furthermore, patterns other than the polar pattern that usually arises first in a growing one-dimensional syst6m described by Turing's model can be obtained. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 10 publications
0
57
1
Order By: Relevance
“…This semi-scale invariance is particularly significant in that it allows regulation, a property of many biological systems, whereby a specific number of pattern elements is laid down despite significant variation in the domain size and without the need to finely tune parameter values. Various authors have considered the problem of scale invariance in reaction-diffusion systems (Othmer and Pate, 1980;Hunding and Sørensen, 1988) and have concluded that some form of feedback from the domain size into the kinetic parameters is necessary, requiring close parameter tolerances. The semi-scale invariance in the present system arises as a natural consequence of the sequence formation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This semi-scale invariance is particularly significant in that it allows regulation, a property of many biological systems, whereby a specific number of pattern elements is laid down despite significant variation in the domain size and without the need to finely tune parameter values. Various authors have considered the problem of scale invariance in reaction-diffusion systems (Othmer and Pate, 1980;Hunding and Sørensen, 1988) and have concluded that some form of feedback from the domain size into the kinetic parameters is necessary, requiring close parameter tolerances. The semi-scale invariance in the present system arises as a natural consequence of the sequence formation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…There are several ways in which this can be done, and here we focus on one possibility. The composite model that we consider is one in which the spatial variation in diffusion coefficients is controlled by a regulatory chemical c. In our model we assume, as before, that the diffusion coefficient of u is constant, but we now assume that the diffusion coefficient of v is modulated by c. This could, for example, reflect an increase in gap junction permeability for v due to the presence of c (Othmer & Pate, 1980). We consider a mechanism for the production of c, in which c is secreted at one end of the domain, diffuses and is degraded throughout the domain, but does not flow through the other boundary.…”
Section: Smoothly Varying Diffusion Coefficientmentioning
confidence: 99%
“…In this paper we consider how an underlying spatial prepattern in diffusion coefficients modifies the pattern forming properties of a reaction-diffusion model. In developmental biology, spatial variation in morphogen diffusivity may be controlled by the concentration of a regulatory chemical which, for example, affects morphogen transport by binding to the morphogen or by modulating gap junction permeability (Othmer & Pate, 1980, Hunding & Serenson, 1988Brummer et al, 1991). Several authors have investigated numerically the effects of spatially varying reaction terms in reaction-diffusion systems (Gierer & Meinhardt, 1972;Hunding et al, 1990, Lacalli, 1990) and the effects of spatially varying diffusion (Hunding, 1987(Hunding, , 1989.…”
Section: Introductionmentioning
confidence: 99%
“…However, appropriate changes must also be made to the input flux , lest the profile will increase or decrease in amplitude depending on whether diffusion or decay rates are modified. We have previously analyzed this system in detail and refer the interested reader to Othmer et al, 1980, Umulis et al 2008 and Umulis 2009 [6], [7], [8]. Herein we focus on an alternative and remarkably simple mechanism that confers approximate scale invariance in Drosophila embryos.…”
Section: A the Governing Equationsmentioning
confidence: 99%